Ekonomi Syari’ah Versus Ekonomi Konvensional - Suwadji (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam, 2014)
What distinguishes an economy mode sharia (Islamic economics) with conventional economics? At first glance may be indifferent, but if explored further, there is a fundamental difference between the two. To find out will it be able to begin by comparing the basic principles of both, roughly where the similarities and differences.